In our time: Memoir of a revolution - Brownmiller, Susan (Dial Press, 1999)
There once was a time when the concept of equal pay for equal work did not exist, when women of all ages were "girls," when abortion was a back-alley procedure, when there was no such thing as a rape crisis center or a shelter for battered women, when "sexual harassment" had not yet been named and defined. "If conditions are right," Susan Brownmiller says in this stunning memoir, "if the anger of enough people has reached the boiling point, the exploding passion can ignite a societal transformation." In Our Time tells the story of that transformation, as only Brownmiller can. A leading feminist activist and the author of Against Our Will, the book that changed the nation's perception of rape, she now brings the Women's Liberation movement and its passionate history vividly to life. Here is the colorful cast of characters on whose shoulders we stand–the feminist icons Betty Friedan, Kate Millett, Germaine Greer, and Gloria Steinem, and the lesser known women whose contributions to change were equally profound. And here are the landmark events of the era: the consciousness-raising groups that sprung up in people's living rooms, the mimeographed position papers that first articulated the new thinking, the abortion and rape speak-outs, the daring sit-ins, the underground newspaper collectives, and the inventive lawsuits that all played a role in the most wide-reaching revolution of the twentieth century. Here as well are Brownmiller's reflections on the feminist utopian vision, and her dramatic accounts, rendered with honesty and humor, of the movement's painful internal schisms as it struggled to give voice to the aspirarations of all women. Finally, Brownmiller addresses that most relevant question: What is the legacy of feminism today?
Keywords: 1900-1999; amériques; approches et analyses; cours; discipline; droits des femmes*; fem1000; féminisme matérialiste; féminisme radical; histoire; mouvements féministes; premier cycle; périodes historiques; régions géographiques; sciences humaines; thématiques; témoignage; états-unis

De la clandestinité à l'affirmation : pour une histoire de la communauté gaie montréalaise - Higgins, Ross (Comeau & Nadeau, 1999)
Survol historique de la communauté gaie-lesbienne de Montréal. D'après l'auteur, ce premier volume sera suivi d'une publication ultérieure où son enquête sera présentée de façon plus globale.
Section: 165, [2] p
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; his4860; histoire; histoire et politique; hétérosexisme; identités LGBTQIA2+; justice sociale; militance; montréal; premier cycle; périodes historiques; queer; québec; régions géographiques; sciences humaines; shm4000; soc2014; systèmes d'oppressions; thématiques

Femmes du siècle - Institut de recherches et d'études féministes (FéminÉtudes, 1999)
Cette publication de 1999 porte sur l’histoire des féminismes. *** FéminÉtudes est une revue étudiante, féministe et multidisciplinaire. La revue est née en 1995 de l’initiative d’étudiantes féministes dans l’intérêt de partager leurs recherches et de créer un groupe affinitaire. La revue est dirigée par des collectifs de rédaction bénévoles et autogérés, et soutenue par l’Institut de Recherches en Études Féministes (IREF) de l’Université du Québec à Montréal. Au fil des ans, FéminÉtudes a réussi à se bâtir une réputation et une légitimité dans le champ de la recherche en études féministes, tout en offrant une tribune au travaux et aux réflexions de dizaines d’étudiant.e.s. Au-delà de la recherche, c’est également pour l’avancement des luttes féministes que FéminÉtudes souhaite continuer à grandir.
Disponible en libre accès : https://iref.uqam.ca/feminetudes/vol-4-no-1-1999-femmes-du-siecle/
Keywords: 1900-1999; 1990-1999; amériques; discipline; féminétudes; histoire; histoire des femmes*; histoire et politique; militance; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; thématiques